Charter and Revised Ordinances of the City of Glasgow 64-65 (1903) - (:unkn) unknown (My University, 1903)
Chapter 16-Misdemeanors, § 11-Carrying Concealed Weapons: If any person shall in this city carry concealed upon or about his person any deadly or dangerous weapon, or shall go into any church or place where people have assembled for religious worship, or into any school§ room or place where the people are assembled for educational, literary or social purposes, or to any election precinct on any elec§tion day, or into any court-room during the sitting of court, or into any other public assemblage of persons met for any lawful pur§pose other than for militia drill, or meeting called under militia law of this state, having upon or about his person any kind of fire§ arms, bowie knife, dirk, dagger, slung-shot or other deadly weap§on, or shall, in the presence of one or more person, exhibit any such weapon in a rude, angry or threatening manner, or shall have or carry any such weapon upon or about his person when intoxi§cated, or under the influence of intoxicating drinks, or shall, di§rectly or indirectly, sell or deliver, loan or barter to any minor any such weapon, without the consent of the parent or guardian of such minor, he shall, upon conviction, be punished by a fine of not less than fifty nor more than one hundred dollars: Provided this section shall not apply to police officers, nor to any officer or person whose duty it is to execute process or warrants, or to sup§press breaches of the peace, or to make arrests."
Keywords: BRANDISHING; CARRY - CONCEALED; SENSITIVE PLACES; TRANSFER - MINORS